Stoi na stacji [Auschwitz] lokomotywa... - Wachuła, Michał (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article refers to connection between Julian Tuwim's and Stanisław Wygodzki's poems of the same title - Lokomotywa. The aim is to show evolution of the image of railway in the consciousness of the modern man, as well as to show to what extent the World War II affected the perception of the railway. Is it still an icon of modernity, or maybe an icon of death?
Keywords: postęp; dehumanizacja; Holocaust; ikona nowoczesności; lokomotywa; nazistowskie pociągi śmierci; rewolucja przemysłowa; Sonderzüge; topos pociągu śmierci; trainspotting; Zagłada; progress; dehumanization; icon of modernity; locomotive; nazi death trains; industrial revolution; death train topos; Extermination